Strategic approaches for conflict resolution in organizations emerging research and opportunities - Bhattacharyya, Siddhartha, 1975- (Advances in business strategy and competitive advantage., 2019)
"This book examines emerging approaches for conflict resolution in organizations"--Provided by publisher"--